Non-Covalent Interactions in Hexanuclear Polyoxidometalates [Viv6b20o50h8]8−. an Experimental and Theoretical Approach - Venegas-Yazigi, D; Venegas-Yazigi, D; Muñoz-Becerra, K; Muñoz-Becerra, K; Wrighton-Araneda, K (Elsevier Ltd, 2022)
A complete study of the optical and magnetic properties of three new {V6-type} polyoxidometalates (NH3CH2CH2CH2NH3)4{V6B20O50H8}·4H2O 1, K2(NH3CH2CH2NH3)2.5(NH3CH2CH2NH2){V6B20O50H8}·2H2O 2, and K2(NH3CH2CH2CH2NH3)2(H3O)2{V6B20O50H8}·8H2O 3 is presented. Using TD-DFT calculations, the assignment of the experimental UV–Visible spectra was established with four absorption bands: a higher in energy assigned to metal-to-metal charge transfer and the remaining associated principally to d-d transitions, demonstrating that the {V6IVO18}12− ring is the principal chromophore for these systems and that the surrounding packing does not have an influence on it. On the other hand, the differences observed in the magnetic properties are caused by the influence of the non-covalent interactions between the potassium ions with some oxygen atoms of the VIV coordination spheres, thus modifying the VIV-VIV exchange coupling. This effect was demonstrated using a simplified binuclear DFT model that predicts a higher VIV-VIV antiferromagnetic coupling when the K cations become closer to the oxygen bridge atoms that link the VIV centres of the {V6IVO18}12− ring. © 2021